Life after literature: Jorge Semprún's narrative afterlives. Issue 1 (March 2020) - Tynan, Avril
Abstract : Against the Aristotelian tradition of tragic plot, this article argues that beginning may not lead to the end in any teleological manner but may instead defer the arrival of the end, deconstructing historical and autobiographical narrative structures. In the work of Jorge Semprún, whose corpus attests to the complexities of narrating the twentieth century, the act of beginning is caught up with the author's endless rewriting, so that each new narrative beginning attests to a failure to conclude the previous work, to tell the 'whole' story. In two works of fiction, La Montagne blanche ['The White Mountain'] (1986) and Netchaïev est de retour ['Nechayev is back'] (1987), the beginning intentionally defers the ending through a structural and semantic circularity. At stake is an understanding of how beginning may not anticipate closure but may instead be harnessed to prevent it, inviting the reader to continue the work of memory as an embodied co-participant.